Inflation and GDP Dynamics in Production Networks: A Sufficient Statistics Approach - Hassan Afrouzi; Saroj Bhattarai (Center for Economic Studies and ifo Institute (CESifo), 2023)
We derive closed-form solutions and sufficient statistics for inflation and GDP dynamics in multi-sector New Keynesian economies with arbitrary input-output linkages. Analytically, we decompose how production linkages (1) amplify the persistence of inflation and GDP responses to monetary and sectoral shocks and (2) increase the pass-through of sectoral shocks to aggregate inflation. Quantitatively, we confirm the significant role of production networks in shock propagation, emphasizing the disproportionate effects of sectors with large input-output adjusted price stickiness: The three sectors with the highest contribution to the persistence of aggregate inflation have consumption shares of around zero but explain 16% of monetary non-neutrality.
Keywords: E32; E52; C67; 330; production networks; multi-sector model; sufficient statistics; inflation dynamics; real effects of monetary policy; sectoral shocks